Ocimum basilicum (Basil) Modulates Apoptosis and Neurogenesis in Olfactory Pulp of Mice Exposed to Chronic Unpredictable Mild Stress - Ayuob, Nasra N.; Balgoon, Maha J.; Ali, Soad; Alnoury, Ibrahim S.; ALmohaimeed, Hailah M.; AbdElfattah, Amany A. (Frontiers in Psychiatry, 2020)
Background: Ocimum Basilicum (O. Basilicum) have been described to have antidepressant and anxiolytic activities. Although a relationship between the main olfactory bulb (MOB) and depression has been known for sometimes, the chronic stress-induced dysfunction of the MOB has not been clearly described. Objectives: This study aimed to assess the efficacy of inhalation of O. Basilicum essential oils in improving chronic unpredictable mild stress (CUMS)-induced changes in MOB of mice and understand the mechanism underlying such effects. Materials and methods: Adult male mice (n=40) were assigned into four groups included the control, CUMS-exposed, CUMS + Fluoxetine (FLU), CUMS + O. Basilicum. Behavioral changes, serum corticosterone level and gene expression of GFAP, Ki 67 and Caspase-3 were assessed using RT-PCT. Histopathological and immunochemical examination of the MOB was performed. Results: FLU and O. Basilicum significantly down-regulated (p = 0.002, p<0.001) caspase-3 gene expression indicating reduced apoptosis and up-regulated (p = 0.002, p < 0.001) Ki67 gene expression indicating enhanced neurogenesis in MOB, respectively. FLU and O. Basilicum-treated mice markedly improved MOB mitral cell layer distortion and shrinkage induced by CUMS. Conclusion: O. Basilicum relieved both biochemical and histopathological chronic stress-induced changes in the main olfactory bulb possibly through up-regulation of gene expression of GFAP and Ki67 and down-regulation of Caspase-3 in the MOB.